Development of Adventure Multimedia Game Based on Mobile Learning in Pyramid Topic for Junior High School - Ismail Djakaria; Ukhti Nurfajriah Sasmita Ijonu; Sumarno Ismail (Didaktik Matematika, 2021)
Mathematics is a difficult subject for students, causing low motivation, interest and student learning outcomes. To attract students to be more interested in learning mathematics, they must use interactive learning media so that learning is not boring and fun. This study aims to develop a multimedia adventure game in pyramid topic based on mobile learning in grade eight. This study uses the 4-D development model, however, at the stage of dissemination only limited distribution is carried out. The subjects in this study were grade eight students of one of junior school in Gorontalo District, Gorontalo Province, Indonesia. The results of the study based on the validation of topic and media experts showed that the quality of multimedia was good. Meanwhile, based on the teacher's ability for managerial to learn is also categorized as good, the activities of students during the learning process reach the ideal time criteria, the responses of all students are classified as very positive of 90.56% and learning tests show that 72.5% of students achieve completeness. This shows that the adventure multimedia game based on mobile learning in pyramid topic is valid, practise, and effective.